Vulnerabilities in Social Assistance System - BREAZ, MARIA-ALINA (2024)
In recent years, Romania has made significant progress in various aspectsof its social and economic development. However, one pressing issue thatcontinues to demand attention is the well-being of its vulnerable children.Despite efforts to improve the situation, many children in Romania stillface a range of challenges that affect their development, education, andfuture prospects. One of the major issues is the high number of childrenliving in poverty. Economic disparities in the country have left asubstantial portion of the population struggling to meet basic needs.